2017
DOI: 10.1093/aob/mcx036
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional intracellular structure of a whole rice mesophyll cell observed with FIB-SEM

Abstract: Cellular and sub-cellular ultrastructures of a whole mesophyll cell in a rice leaf blade are demonstrated three-dimensionally using a FIB-SEM. The 3-D models and numerical information support the hypothesis that rice mesophyll cells enhance their CO 2 absorption with increased cell surface and sheet-shaped chloroplasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
2
36
0
1
Order By: Relevance
“…The sequential images were used for the reconstruction of 3D images (Figure ). In this study, the protocols to enhance signals for the backscatter electron imaging of resin‐embedded tissue (Ichimura et al, ) were not applied, because sufficient contrast was available for the observation of chloroplasts (Oi et al, ). The chloroplast structure of control was flat, and no protruded bodies were observed (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequential images were used for the reconstruction of 3D images (Figure ). In this study, the protocols to enhance signals for the backscatter electron imaging of resin‐embedded tissue (Ichimura et al, ) were not applied, because sufficient contrast was available for the observation of chloroplasts (Oi et al, ). The chloroplast structure of control was flat, and no protruded bodies were observed (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Oi et al () reported a doughnut‐shaped chloroplast formed under a moderate growth condition, which is the structure related to surrounding other organelles. The doughnut shape would be formed by the curvature of the chloroplast itself along the cell lobe, and thus, the portion of the chloroplast body surrounding other organelles contains thylakoid membranes (Oi et al, ). On the other hand, a chloroplast pocket would be formed by a large sheet structure, which was a thin layer without thylakoid membranes in a cross section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional leaf structures also have been explored using synchrotron radiation X‐ray laminography (Ho et al , ), microcomputed tomography imaging (Théroux‐Rancourt et al , ) and the incorporation of a focused ion beam (FIB) system within the SEM chamber which etches away atoms on the specimen surface (FIB‐SEM) (e.g. Jin et al , ; Oi et al , ; Reagan et al , ; Yamane et al , ). However, these 3D techniques have not been widely applied to date, which may limit our understanding of leaf anatomy (Théroux‐Rancourt et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in mesophyll cells the vacuole is small or even absent. Most cells contain more chloroplasts [30] with smaller and denser intracellular spaces than those of hypocotyl cells, meaning they can withstand greater osmotic pressure. Therefore, it is speculated that the osmotic pressures tolerated by the two are also different due to differences in spatial composition between hypocotyl cells and mesophyll cells, resulting in a difference in the suitable mannitol concentration.…”
Section: Discussionmentioning
confidence: 99%